Precious gifts : a novel / Danielle Steel. - Steel, Danielle (Delacorte Press, 2015)
"Handsome, widowed, sophisticated, utterly charming, Paul Parker won the heart of a wealthy young Frenchwoman--the daughter of an American financier, the granddaughter of a major French art dealer--as his second wife. In two marriages, he fathered a challenging son and three very different daughters. But as irresponsible as he was irresistible, he ultimately shrugged off the demands of marriage and parenting to pursue life as an international bon vivant... Now, after a long illness, Paul has slipped away peacefully in his sleep, and his family has gathered together to read his will... He has made a very personal bequest to each of his children, carefully designed to help them achieve their own unique dreams and find true happiness. But Paul has saved the biggest surprise for his ex-wife Véronique: a secret from the past that shakes her world and sets her free."--Book jacket.